Terbinafine Resistance of Trichophyton Clinical Isolates Caused by Specific Point Mutations in the Squalene Epoxidase Gene - Yamada, Tsuyoshi (Antimicrob Agents Chemother, 2017)
Terbinafine is one of the allylamine antifungal agents whose target is squalene epoxidase (SQLE). This agent has been extensively used in the therapy of dermatophyte infections. The incidence of patients with tinea pedis or unguium tolerant to terbinafine treatment prompted us to screen the terbinafine resistance of all Trichophyton clinical isolates from the laboratory of the Centre Hospitalier Universitaire Vaudois collected over a 3-year period and to identify their mechanism of resistance. Among 2,056 tested isolates, 17 (≈1%) showed reduced terbinafine susceptibility, and all of these were found to harbor SQLE gene alleles with different single point mutations, leading to single amino acid substitutions at one of four positions (Leu(393), Phe(397), Phe(415), and His(440)) of the SQLE protein. Point mutations leading to the corresponding amino acid substitutions were introduced into the endogenous SQLE gene of a terbinafine-sensitive Arthroderma vanbreuseghemii (formerly Trichophyton mentagrophytes) strain. All of the generated A. vanbreuseghemii transformants expressing mutated SQLE proteins exhibited obvious terbinafine-resistant phenotypes compared to the phenotypes of the parent strain and of transformants expressing wild-type SQLE proteins. Nearly identical phenotypes were also observed in A. vanbreuseghemii transformants expressing mutant forms of Trichophyton rubrum SQLE proteins. Considering that the genome size of dermatophytes is about 22 Mb, the frequency of terbinafine-resistant clinical isolates was strikingly high. Increased exposure to antifungal drugs could favor the generation of resistant strains.